Novel mutations in the ZEB1 gene identified in Czech and British patients with posterior polymorphous corneal dystrophy - Liskova, Petra; Tuft, Stephen J; Gwilliam, Rhian; Ebenezer, Neil D; Jirsova, Katerina; Prescott, Quincy; Martincova, Radka; Pretorius, Marike; Sinclair, Neil; Boase, David L; Jeffrey, Margaret J; Deloukas, Panos; et al. (Human mutation, 2007)
We describe the search for mutations in six unrelated Czech and four unrelated British families with posterior polymorphous corneal dystrophy (PPCD); a relatively rare eye disorder. Coding exons and intron/exon boundaries of all three genes (VSX1, COL8A2, and ZEB1/TCF8) previously reported to be implicated in the pathogenesis of this disorder were screened by DNA sequencing. Four novel pathogenic mutations were identified in four families; two deletions, one nonsense, and one duplication within exon 7 in the ZEB1 gene located at 10p11.2. We also genotyped the Czech patients to test for a founder haplotype and lack of disease segregation with the 20p11.2 locus we previously described. Although a systematic clinical examination was not performed, our investigation does not support an association between ZEB1 changes and self reported non-ocular anomalies. In the remaining six families no disease causing mutations were identified thereby indicating that as yet unidentified gene(s) are likely to be responsible for PPCD.
Keywords: DNA Mutational Analysis; Male; transkripční faktor Zeb1; Pedigree; mutace; rodokmen; dědičné dystrofie rohovky; United Kingdom; Adolescent; Česká republika; vzácné nemoci; Collagen Type VIII; Zinc Finger E-box-Binding Homeobox 1; oční proteiny; Adult; Aged; dospělí; mužské pohlaví; senioři; mutační analýza DNA; mladiství; Czech Republic; lidé; Transcription Factors; ženské pohlaví; transkripční faktory; Humans; Eye Proteins; Spojené království; Corneal Dystrophies, Hereditary; kolagen typ VIII; Mutation; Homeodomain Proteins; Female; lidé středního věku; homeodoménové proteiny; Rare Diseases; Middle Aged